British protectionism and oil industry prior to the establishment of Petronas - Saiful Khairi Kamarudin, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The existence of protectionism policy in Malaya and Borneo had been practised by the British specifically in the oil industry during colonialism. This policy was to prevent the largest American oil corporation, from dominating the oil market in Southeast Asia. The two British oil companies, the Anglo-Saxon Company and Shell Company in the early 20th century completed their business relationship with the Dutch oil company to control the oil industry in Southeast Asia. Oil producer colonies in Southeast Asia was solely granted oil supply through British oil company to prepare the outbreak of the First World War. This marked the height of British protectionism by providing continuous oil supply to the British Navy and expanding oil exports during the First World War. Later, PETRONAS adopted protectionism and monopoly strategies to increase equity ownership of Malays in the oil and mining industry.